La vida humana entre la perfección y la caída según san Agustín - Calabrese, Claudio César, 1959-‏ (2008)
In this analysis of St. Augustine’s concept of natural law, the focus will be on the way he presents, in a continuous development, the ideas of moral compulsion and personal growth. In Augustine’s interpretation of the biblical text, the foundations of natural law are provided, such that morality is not simply the fruit of consensus. Man is seen not only as a product of history, even though he cannot be understood outside of it. The natural order and the supernatural order are this way tied together.
Keywords: Agustín, -- Santo, Obispo de Hipona; Moral cristiana